Endocrine and body composition changes across a competitive season in collegiate speed-power track and field athletes - Mangine, G. T.; Eggerth, A.; Gough, J.; Stratton, M. T.; Feito, Y.; van Dusseldorp, T. A. (The Journal of Strength and Conditioning Research, 2021)
Maintaining lean mass is important for track and field (TF) athletes who compete in speed-power events, but little is known about how lean mass and related hormones might change over an 8- to 10-month collegiate season. Therefore, to monitor changes in free testosterone (T), cortisol (C), and body composition in TF athletes across their entire competitive season, 9 female (20.3 ± 1.2 years, 169 ± 5 cm, and 67.6 ± 8.5 kg) and 7 male (21.1 ± 2.0 years, 181 ± 9 cm, and 77.3 ± 5.9 kg) Division I TF athletes provided resting and fasted blood samples at the onset of their indoor season (baseline), before and on returning from the indoor conference championships (ICCs), at the beginning and end of a heavy midseason training week (HVY), and before leaving for the National Collegiate Athletic Association (NCAA) Championships. Body composition was also assessed at each of these periods using a 4-compartment model. Except for a 20% reduction (p = 0.030) from ICCs to the onset of HVY in men only, linear mixed models with repeated measures did not reveal any changes in hormone concentrations. Compared with baseline, an overall increase in fat-free mass was observed at HVY (~2.74%, p = 0.023) before it reduced by 3.81% before the NCAA Championships (p = 0.022). Despite variations in training and competition, resting concentrations of hormones indicative of anabolic status remained relatively consistent over the course of an entire season in speed-power TF athletes. Coaches and athletes may consider monitoring these variables to assess the athlete's response to the changing demands of a competitive season.